Multibank holding companies and bank stability - Radoslav Raykov; Consuelo Silva-Buston (Bank of Canada, 2018)
This paper studies the relationship between bank holding company affiliation and the individual and systemic risk of banks. Using the 2005 hurricane season in the US as an exogenous shock to bank balance sheets, we show that banks that are part of a holding parent company are more resilient than independent banks. Examining the impact of the liquidity of the holding on resiliency shows that banks are more fragile when the liquidity of the holding is lower, consistent with internal capital markets playing a role in stabilizing banks. We also show that banks whose holdings display low liquidity levels rebalance their portfolios towards riskier activities, such as non-traditional banking activities.
Keywords: G1; G2; 330; Financial stability; financial institutions